DEVELOPING E-LEARNING MEDIA WITH MOODLE FOR STUDENT OF CLASS VII ON SUBJECT MATTER OF TRIANGLE - Ahmadun Fajar Hidayat; Uus Kusdinar (Universitas Ahmad Dahlan, 2019)
Teachers are required to innovate in the learning process, which is a determinant of students' ability to understand the classroom materials. One of the innovations is to make learning media, but in reality, the availability of available media is still limited. The research aims to design, create, and describe whether or not e-learning based mathematics learning media use moodle on triangle material for grade VII students. This research is focused on the development of mathematics learning media, which is packaged in internet form. This development research using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). His research subjects are material experts, media experts, and students response of Junior High School (SMP) 1 Muhammadiyah Prambanan and SMP Muhammadiyah 17 Prambanan Klaten. Data collection techniques used interviews, questionnaires, and observations. The research instruments used are observation guides, interview guides, and questionnaires to assess the learning media that has been developed. The data analysis technique uses qualitative. This research has succeeded in developing math learning media that have excellent quality (SB). The average score of expert material assessment 74.3333, and the average score of media expert assessment results was 113.33. While the student response score 83.043 with scores on small class trials and large class trials. So the average score of idealization is 270,706 from the ideal maximum score of 315. Based on these assessments, this math learning media is worthed to be used as a learning resource.